Periodontitis as a causative agent for systemic disease of pancreas - Jain, Sweeti; Sharma, Veena; Gupta, M K; Tailang, Mukul; Pathak, A K (Recent Research in Science and Technology, 2013)
In recent years it has been studied that periodontal diseases have a strong correlation with systemic health. The purpose of the present study is to correlate the periodontitis with the pancreatic health. Two hundred sixty subjects were selected for this study and divided in control and chronic periodontitis. Amylase, lipase, glucose, cholesterol, sodium, potassium and calcium level were measured in serum of all subjects. Significant changes were observed in amylase, glucose, cholesterol and calcium levels in periodontitis subjects.